Ergonomic clothing design for care-dependent elderly women - Caldas, Artemisia (2019)
This paper describes the development of ergonomic clothing suitable for the corporal characteristics of the care-dependent elderly women at four institutions: two located in the city of Guimaraes (Portugal) and two in the city of Teresina (Brazil). The prototypes were developed based on the needs of the elderly according to some functional factors as well as their physical conditions, aiming at easier handling by the caregiver and comfort for the user. Below, the functional properties of the applied fabrics and accessories, the modeling process, and the garment assembly are described.